Inside Back Cover: "Two‐Step" Raman Imaging Technique To Guide Chemo‐Photothermal Cancer Therapy (Chem. Eur. J. 48/2015). Issue 48 (23rd November 2015) - Deng, Lin; Li, Qiujin; Yang, Yang; Omar, Haneen; Tang, Naijun; Zhang, Jianfei; Nie, Zhihong; Khashab, Niveen M.
Abstract : A surface‐enhanced Raman scattering technique is introduced to track the uptake of doxorubicin (DOX)‐loaded on a new graphene oxide (GO)/gold nanorod hybrid material and the real‐time pharmacokinetics of DOX release into cells in order to find the best time to apply photothermal therapy to maximize the outcome of the therapy. For more details see the Full Paper by N. M. Khashab et al. onpage 17274 ff.